Where Do Fires Burn More Intensely? Modeling and Mapping Maximum MODIS Fire Radiative Power from Aboveground Biomass by Fuel Type in Mexico - Diana Aime Tinoco-Orozco; Daniel José Vega-Nieva; Jaime Briseño-Reyes; Mesías Edwin Dominguez-Amaya; Adrián Israel Silva-Cardoza; Carlos Ivan Briones-Herrera; Juan Gabriel Álvarez-González; José Javier Corral Rivas; Pablito Marcelo López-Serrano; Enrique J. Jardel-Pelaez; Diego Perez-Salicrup; Ana Daría Ruiz-González (Fire)
Mapping potential fire intensity is a fundamental tool for fire management planning. Despite the wide use of Fire Radiative Power (FRP) as an indicator of expected fire intensity and fire emissions, very few studies have spatially analyzed the role of remotely sensed proxies of vegetation productivity to explain FRP. The current study aimed at modeling and mapping the relationships between aboveground biomass and Moderate Resolution Imaging Spectroradiometer (MODIS) maximum FRP, at 1 km pixel, in 2011–2020, for each of 46 fuel regions in the entirety of Mexico. Maximum FRP–biomass relationships supported a novel hypothesis of varying constraints of fire intensity. In lower-productivity areas, such as semiarid shrub- and grass-dominated ecosystems, fine fuel loads limited fire occurrence and FRP was positively related to biomass. In the more productive areas, such as temperate or tropical forests, a humped relationship of FRP against biomass was observed, suggesting an intermediate-productivity hypothesis of maximum fire intensity within those regions. In those areas, the highest fire intensity was observed in the intermediate biomass areas, where surface (timber understory) and crown fuel availability, together with higher wind penetration, can result in crown fires. On the contrary, within the most productive areas, the lowest intensity occurred, likely due to weather and fuel (timber litter) limitations.